SINKRETISME HUKUM ISLAM DAN HUKUM ADAT DALAM TRADISI MAHAR SEKATI MESA TEDONG DI KALUKKU SULAWESI BARAT - laela safriani (LPPM STAI Muhammadiyah Probolinggo, 2026)
This article examines the syncretism between Islamic law and local customary norms in the dowry tradition of Sekati Mesa Tedong in Kalukku District, West Sulawesi. This dowry practice serves not only as a symbol of responsibility and respect toward the bride but also as a reflection of the community’s cultural identity, with its form and value shaped by inherited customary norms. The study aims to analyze the forms of Sekati Mesa Tedong, explore the perspectives of the community and religious leaders on the integration of customary values and Islamic legal principles within the tradition, and evaluate its conformity with Islamic law. The research employs a qualitative approach using a juridical-empirical method through observation, interviews, and documentation.The findings indicate that Sekati Mesa Tedong is practiced in two forms: the original form, consisting of a roll of kaci cloth and a buffalo, and an adapted form involving money, land, or other valuable items agreed upon by both parties. Community members and religious leaders view this tradition as a harmonious blend of adat and Islamic teachings, as long as it is based on sincerity and does not impose an excessive burden on the groom. From the perspective of Islamic law, the Sekati Mesa Tedong tradition does not conflict with the Sharia, as it upholds the principles of mutual consent (taradhi), fairness, and deliberation, thereby illustrating a form of legal syncretism that reflects the integration of religious values and local cultural norms.